Implementation of a Conventional Lightning Protection System in a Village Government Building in Bogor: A Community Engagement Approach - Suryadi, Aris; Rodiah Machdi, Agustini; Yamato, Yamato; Budi Rijadi, Bloko; Nur Fajri, Zulfan; Fajar Ariyanto, Ilham (Universitas Ahmad Dahlan, 2025)
Background: This article presents the implementation of a lightning protection system at the Cibanon Village Hall in Bogor as part of a technology-based community service program. Contribution: The initiative to install a conventional lightning rod in the Cibanon Village Hall building to protect electronic equipment. Method: The methodology includes site assessment, risk analysis, system design, and installation following international standards. Results: The results obtained from this study are the area that has the potential for lightning strikes, so it is recommended to install a conventional lightning rod installation with 4 (four) lightning rods on top of the building and 1 (one) rod in the ground with a depth of 7.5 m with a grounding resistance value of 2.02 Ohm. Conclusion: Shows the level of security requirements for the Cibanon Village Hall building against lightning strikes. The initiative also fostered community awareness and participation, highlighting its replicability in other rural areas with similar environmental threats.